2023
DOI: 10.1101/2023.01.25.525432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating the roles of reflexes and central pattern generators in the control and modulation of human locomotion using a physiologically plausible neuromechanical model

Abstract: Studying the neural components regulating movement in human locomotion is obstructed by the inability to perform invasive experimental recording. Neuromechanical simulations can provide insights by modeling the locomotor circuits. Past neuromechanical models proposed control of locomotion either driven by central pattern generators (CPGs) with simple sensory commands or by a purely reflex-based network regulated by state-machine mechanisms. However, the physiological interpretation of these state-machines rema… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Thus, if the reflexes and the anatomy of the distal leg are improperly integrated with the rest of the system, the dynamics at this joint may be affected. For example, Dzeladini et al [2014], Di Russo et al [2023], and Ramadan et al [2021] presented models with alterations at the ankles, the two last having discrepancies resembling those in the MPL model. Schumacher et al [2023] has shown results matching consistently with the kinematic data, but also presented abnormal trajectories for the ankle that were depending on the selection of the musculoskeletal model.…”
Section: Speed Transitionsmentioning
confidence: 95%
See 4 more Smart Citations
“…Thus, if the reflexes and the anatomy of the distal leg are improperly integrated with the rest of the system, the dynamics at this joint may be affected. For example, Dzeladini et al [2014], Di Russo et al [2023], and Ramadan et al [2021] presented models with alterations at the ankles, the two last having discrepancies resembling those in the MPL model. Schumacher et al [2023] has shown results matching consistently with the kinematic data, but also presented abnormal trajectories for the ankle that were depending on the selection of the musculoskeletal model.…”
Section: Speed Transitionsmentioning
confidence: 95%
“…Thus, if the reflexes and the anatomy of the distal leg are improperly integrated with the rest of the system, the dynamics at this joint may be affected. For example, Song and Geyer [2015], Di Russo et al [2023], and Ramadan et al [2021] presented models with alterations at the ankles, the two last having discrepancies resembling those in the MPL model. Geyer and Herr [2010] presents ankle kinematics that fit better experimental data than our model, and Dzeladini et al [2014] have also a better trajectory, especially if the controller is reflex-dependent.…”
Section: Speed Transitionsmentioning
confidence: 95%
See 3 more Smart Citations